Differential Development of Children’s Understanding of the Cardinality of Small Numbers and Zero - Pixner, Silvia; Dresen, Verena; Moeller, Korbinian (Frontiers in Psychology, 2018)
Counting and the understanding of cardinality are important steps in children’s numerical development. Recent studies indicated that language and visuo-spatial abilities play an important role for the development of children’s cardinal knowledge of small numbers. However, predictors for the knowledge of zero were usually not considered in these studies. Therefore, the present study investigated whether the acquisition of cardinality knowledge on small numbers and the concept of zero share cross-domain and domain-specific numerical predictors. Particular interest was paid to the question whether visuo-spatial abilities – in addition to language abilities – were associated with children’s understanding of small numbers and zero. Accordingly, we assessed kindergarteners aged 4 to 5 years regarding their understanding of small numbers and zero as well as their visuo-spatial, general language, counting, Arabic number identification abilities, and their finger number knowledge. We observed significant zero-order correlations of vocabulary, number identification, finger knowledge, and counting abilities with both children’s zero knowledge and understanding of the cardinality of small numbers. Subsequent regression analyses substantiated influences of counting abilities on zero knowledge and influences of both counting abilities and finger knowledge on children’s understanding of the cardinaltiy of small number. No significant influences of cross-domain predictors were observed. In sum, these results indicate that domain-specific numerical precursor skills seem to be more important for children’s development of an understanding of the cardinality of small numbers as well as of zero than more proximal cross-domain abilities such as language and visuo-spatial abilities.